The MOZ-BRPF1 acetyltransferase complex in epigenetic crosstalk linked to gene regulation, development, and human diseases - Viita, Tiina; Côté, Jacques (Frontiers in Cell and Developmental Biology, 2023)
Acetylation of lysine residues on histone tails is an important post-translational modification (PTM) that regulates chromatin dynamics to allow gene transcription as well as DNA replication and repair. Histone acetyltransferases (HATs) are often found in large multi-subunit complexes and can also modify specific lysine residues in non-histone substrates. Interestingly, the presence of various histone PTM recognizing domains (reader domains) in these complexes ensures their specific localization, enabling the epigenetic crosstalk and context-specific activity. In this review, we will cover the biochemical and functional properties of the MOZ-BRPF1 acetyltransferase complex, underlining its role in normal biological processes as well as in disease progression. We will discuss how epigenetic reader domains within the MOZ-BRPF1 complex affect its chromatin localization and the histone acetyltransferase specificity of the complex. We will also summarize how MOZ-BRPF1 is linked to development via controlling cell stemness and how mutations or changes in expression levels of MOZ/BRPF1 can lead to developmental disorders or cancer. As a last touch, we will review the latest drug candidates for these two proteins and discuss the therapeutic possibilities.